Low N Deposition Coupled With Climate Warming Promote Soil Asymbiotic N Fixation via Increasing Microbial Specialists in Alpine Grassland - Ke Zhang; Yaoming Li; Ran Zhang; Anna Du; Zuyan Ma; Hang Shi; Juejie Yang; Wenli Ding; Hao Shen; Richard D. Bardgett; Huaiying Yao; Shikui Dong (Global Change Biology, 2026)
Biological nitrogen fixation (BNF) is a vital process for introducing new N into natural ecosystems, and this process has been demonstrated to be suppressed by high N deposition. However, the net ecological effect and underlying mechanisms of BNF under chronic low‐level N deposition, characteristic of terrestrial ecosystems, remain highly uncertain. Given that climate warming is a key environmental change factor concurrent with N deposition, it is important to investigate whether climate warming can change BNF activity and alter the effects of N deposition on BNF. To fill these knowledge gaps, we implemented a decade‐long‐term manipulation experiment in an alpine grassland ecosystem with 5 treatments, that is, experimental warming (W), low‐level N deposition (N L ), high‐level N deposition (N H ), combination of climate warming and low‐level N deposition (WN L ) and the control (CK). BNF rate was measured by 15 N 2 isotope discrimination. We found that N L significantly stimulated BNF by 112%, contrasting sharply with the complete suppression under N H . Climate warming alone increased the BNF rate by 123%, while the WN L amplified this effect, stimulating BNF by 234%. Structural equation modeling revealed that WN L selectively favored specific diazotrophic groups ( Desulfovibrio ), whose proliferation directly drove the observed BNF shifts. In this N‐limited alpine grassland, low‐level chronic N deposition, especially when combined with warming, fundamentally shifts the diazotrophic community structure by driving a process of niche contraction. This selection process functionally enriches specialized diazotrophs, resulting in a dramatic, positive feedback that significantly promotes the overall biological nitrogen input. Our findings highlight the potential for increased N inputs under realistic future climate scenarios and provide a scientific basis for precision N management in alpine grasslands, both on the Qinghai‐Tibetan Plateau and worldwide.